A Rapid Approach to Determine Soil Carbon Quality and Its Relationship to Soil Greenhouse Gas Emissions. Issue 3 (4th February 2021) - Baas, Peter; Knoepp, Jennifer D.; Markewitz, Daniel; Mohan, Jacqueline E.
ABSTRACT: Soil organic matter composition controls many microbial processes in the soil matrix. How these processes interact to drive carbon cycling through greenhouse gas fluxes or carbon stabilization through biochemical transformations continues to evolve. From laboratory incubations, it is clear that low molecular weight compounds (LMWCs; e.g. dextrose, mannitol, and trehalose) can have a profound effect on microbially mediated fluxes. However, relationships between LMWCs and soil efflux have been largely unproven in field studies due to methodological constraints. In the current study we developed a novel use of Near Infrared Reflectance Spectroscopy (NIRS) to quantify LMWCs (explaining 38–51% of the variance). Paradoxically, we found dextrose concentrations to be negatively correlated with carbon dioxide fluxes in residential sites while mannitol was positively correlated with carbon dioxide fluxes in agricultural sites. Methane fluxes were strongly correlated with trehalose indicating a potential fungal interaction with bacterial methanogens. We found no clear link between LMWCs on nitrous oxide emissions suggesting inorganic nitrogen is a stronger limiting factor. The results from this study showed how a NIRS-based approach can improve mechanistic understanding of the drivers of soil greenhouse gas fluxes.